SINERGI RUMAH-SEKOLAH-MASYARAKAT DALAM PENGUATAN PEMBELAJARAN PAI BERBASIS KARAKTER: MODEL KOLABORASI TRIPARTIT DI DAERAH BUNGO, JAMBI DI KABUPATEN BUNGO, JAMBI - Kurniawan, Sugeng; Faliza; Sriani; Baili; Yulia Friska, Sonia; Sabli, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Character-based Islamic Religious Education (PAI) often experiences fragmentation due to disconnected roles of home, school, and community in internalizing religious and moral values. This study aims to explore tripartite synergy patterns, construct a collaboration model, and identify supporting and inhibiting factors in strengthening character-based PAI learning in Bungo Regency, Jambi. The research employed a descriptive qualitative case study design grounded in Bronfenbrenner’s social ecology theory and Epstein’s collaboration framework. Subjects consisted of 24 participants (12 PAI teachers, 8 parents, 4 community/religious leaders) from three junior/senior high schools selected purposively. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using reflexive thematic analysis and cross-case synthesis. Findings reveal four tripartite synergy mechanisms: (1) integrated character indicator mapping, (2) structured communication forums leveraging local wisdom and simple digital platforms, (3) community-based experiential learning (social internships, religious projects, youth majelis taklim mentoring), and (4) shared accountability systems through character journals, portfolios, and multi-stakeholder feedback. Supporting factors include the adat bersendi syarak value, community leader commitment, and collaborative school leadership. Inhibiting factors encompass parental time constraints, lack of dedicated budget allocation, digital literacy gaps, and misalignment between formal curriculum demands and informal community practices. The study concludes that the tripartite collaboration model transforms PAI from classroom-bound instruction into a holistic, contextual, and sustainable character formation ecosystem. Policy recommendations include institutionalizing synergy forums, developing collaboration guide modules, aligning regional character education budgets, and strengthening teachers' community pedagogy competencies. Findings contribute to Islamic character education theory and Merdeka Curriculum implementation in semi-urban regions.